2020
DOI: 10.1159/000509446
|View full text |Cite
|
Sign up to set email alerts
|

Modified Technique of Doubly Folded Peritoneal Flap Interposition in Transabdominal Vesicovaginal Fistula Repair: Our Experience of 36 Cases

Abstract: Correction of vesicovaginal fistula (VVF) using interpositional flaps is an established procedure. In open repair, omental flap gives good results. However, its availability in all the cases is questionable. We utilized our technique of doubly folded peritoneal flap and assessed the outcome of the repair. Methods: Retrospective observational study included 36 cases of open VVF repair, performed during 2010-2019. Preoperative clinical examination, cystoscopy, and imaging were performed routinely. Open transvesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Standardized reporting of postoperative complications was performed in only three of the studies. 19 , 23 , 31 All postoperative complications are provided separately for each study in the Supplemental Table 2 . Studies with a standardized assessment of complications (according to the Clavien–Dindo classification) are summarized in Table 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Standardized reporting of postoperative complications was performed in only three of the studies. 19 , 23 , 31 All postoperative complications are provided separately for each study in the Supplemental Table 2 . Studies with a standardized assessment of complications (according to the Clavien–Dindo classification) are summarized in Table 7 .…”
Section: Resultsmentioning
confidence: 99%
“…This new idea was conceived with reference to the theory of gracilis muscle interposition, which has been reported with preferable outcomes. A larger volume of muscle with sufficient blood flow, which interposed between 2 organs, is supposed to play an important role [30]. In addition, we hypothesized that a zigzag-shaped approximation line of muscle layer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructed labor is also an important risk factor of VVF. 10,11 Ojewola et al did transabdominal repair of VVF and reported success rate of 92.1% among those undergoing first time repair and success rate was 95.6% among those having failed previous repair via transvaginal route. 12 Bodner et al conducted study to see outcomes of VVF repair using transabdominal and transvaginal approaches and reported 97.8% success rate of vesico-vaginal fistula repair using transvaginal route while majority of the fistula (60%) were simple, 36% were complex and 4% fistula were complicated in their study.…”
Section: Discussionmentioning
confidence: 99%